Workplace Well-Being Berkontribusi dalam Meningkatkan Engagement Karyawan (Studi Literatur) - Indah Roziah Cholilah (Fakultas Dakwah IAIN Jember, 2019)
Human resources are the most important factor in achieving organizational goals. However, sometimes some kinds of problems ranging from work pressure, low-paying salary, conflicts with colleagues, lack of organizational attention and appreciation, also bullying are often faced by these human resources, especially employees. Such problems can trigger stress on these employees. Therefore, the existing employees need to be perceived significant, not only from physiological aspects but also their psychological aspects. Individuals who are physiologically and psychologically secure will have better skills in determining attitudes, behavior and making decisions. Well-being is more than just happiness and pleasure. Well-being or a feeling of comfort in the workplace (workplace well-being) includes health which covers physiological and psychological symptoms related to the medical context. Prosperous employees will influence their personal growth, life goals, dynamic relationships establishment with the surrounding environment and the ability to make positive social contributions. Employees who have high prosperity level at work will become more cooperative, punctual, efficient, have low chance of slacking off and can work longer hours at the company. Employees will be more enthusiastic in working, displaying high dedication and being able to concentrate fully in carrying out their duties and responsibilities. The well-being felt by employees will create positive emotional situations for their work, and become more meaningful. In the end, employees will become more emotionally attached to their workplaces.